Perbandingan antara Persepsi Implisit dan Ekspresi Eksplisit Mahasiswa dalam EDOM (Evaluasi Dosen oleh Mahasiswa) - Guntur Nurcahyanto; Muhamad Taufik Hidayat; Atika Azzahro Hazima; Achmad Januar Arifin; Putri Pramesti Hening; Annisa Fitri; Tivana Aulia Sasmito (Nur Science Institute, 2025)
Background: The purpose of this study is to prove the difference between explicit expressions and implicit perceptions of students in the EDOM (Lecturer Evaluation by Students) assessment component. Methodology: This study uses a quantitative approach with a comparative design. The data in this study consisted of: (1) EDOM filling data, (2) EDOM refill data, and (3) EDOM interpretation data by the author. The subject and informant in this study are students of the PGSD (Elementary School Teacher Education) Study Program at UMS (University of Muhammadiyah Surakarta). Samples are selected purposively. The validity of the data in this study was ascertained using factor analysis. The data were analyzed using descriptive statistical analysis. Result: From the calculation of the Wilcoxon Signed Ranks test, it shows that there is a difference between explicit expression and implicit perception of students on the criteria of learning methods, interaction with students, and satisfaction levels. Similarly, the comparison of the average scores between explicit expression and students' implicit perceptions showed a significant difference in all criteria with better explicit expression. Recommendation: Further research is recommended to identify the psychological, social, and external factors that influence student non-conformity in EDOM assessments